2008
DOI: 10.1371/journal.pone.0001605
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Hypovolemic Circulatory Collapse by IL-6 Activated Stat3

Abstract: Half of trauma deaths are attributable to hypovolemic circulatory collapse (HCC). We established a model of HCC in rats involving minor trauma plus severe hemorrhagic shock (HS). HCC in this model was accompanied by a 50% reduction in peak acceleration of aortic blood flow and cardiomyocyte apoptosis. HCC and apoptosis increased with increasing duration of hypotension. Apoptosis required resuscitation, which provided an opportunity to intervene therapeutically. Administration of IL-6 completely reversed HCC, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…Strikingly, IL6 exerted potent antiapoptotic effects, affording complete protection of rat neonatal cardiomyocytes from sphingosine-induced death [2]. It has also been demonstrated that in vivo administration of IL6 completely reversed cardiac dysfunction and abrogated cardiomyocyte apoptosis in an experimental model of hypovolemic circulatory collapse [28]. These IL6 survival properties were mediated, at least in part, through activation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, IL6 exerted potent antiapoptotic effects, affording complete protection of rat neonatal cardiomyocytes from sphingosine-induced death [2]. It has also been demonstrated that in vivo administration of IL6 completely reversed cardiac dysfunction and abrogated cardiomyocyte apoptosis in an experimental model of hypovolemic circulatory collapse [28]. These IL6 survival properties were mediated, at least in part, through activation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown beneficial effects of IL-6 deficiency in experimental paradigms of thermal injury, sepsis, and trauma/hemorrhage (13, 14, 15). In contrast, other studies demonstrate that IL-6 administration prevents epithelial cell and cardiomyocyte apoptosis induced by trauma/hemorrhage (16, 17). Systemic infusion of IL-6 following hemorrhagic shock reduces inflammation and injury in the liver and lung (18).…”
Section: Introductionmentioning
confidence: 86%
“…We hypothesize that IL-6, which remains the most predominant myokine yet discovered, has a unique role to play. Recent evidence has shown that very low levels of IL-6 protect mammals from life-threatening conditions induced by severe hemorrhagic shock (3,45,47) and the fact that IL-6 knockout animals are more susceptible to heat stroke (41) provides theoretical support for this hypothesis.…”
Section: Significance and Conclusionmentioning
confidence: 99%